2003
DOI: 10.1002/chem.200390184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of Novel Open‐Cage Fullerenes Having Heteroatom(s) on the Rim of the Orifice

Abstract: A thermal liquid-phase reaction of fullerene C(60) with 3-(2-pyridyl)-5,6-diphenyl-1,2,4-triazine afforded aza-open-cage fullerene derivative 5 having an eight-membered-ring orifice on the fullerene cage. Compound 5 was found to undergo oxidative ring-enlargement reactions with singlet oxygen under photo-irradiation to give azadioxo-open-cage fullerene derivatives 9 and 10, which have a 12-membered-ring orifice, in addition to a small amount of azadioxa-open-cage fullerene derivative 11, which has a 10-membere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
166
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 60 publications
4
166
1
Order By: Relevance
“…5 Recently, Murata and co-workers 4,6 have achieved a very high-yield insertion of molecular hydrogen into the azo-thia-open-cage fullerene (H 2 @ATOCF), 4 shown in Figure 1.In this article we describe 1 H NMR measurements on the endohedral H 2 molecules of H 2 @ATOCF in the solid state. We observe a small anisotropy of the H 2 rotation inside the fullerene cage and estimate the correlation time of the H 2 rotation.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…5 Recently, Murata and co-workers 4,6 have achieved a very high-yield insertion of molecular hydrogen into the azo-thia-open-cage fullerene (H 2 @ATOCF), 4 shown in Figure 1.In this article we describe 1 H NMR measurements on the endohedral H 2 molecules of H 2 @ATOCF in the solid state. We observe a small anisotropy of the H 2 rotation inside the fullerene cage and estimate the correlation time of the H 2 rotation.…”
mentioning
confidence: 92%
“…5 Recently, Murata and co-workers 4,6 have achieved a very high-yield insertion of molecular hydrogen into the azo-thia-open-cage fullerene (H 2 @ATOCF), 4 shown in Figure 1.…”
mentioning
confidence: 99%
“…Owing to this discovery, we could obtain a fullerene derivative 3 with sufficiently large opening [4], and molecular hydrogen was found to get inside the open-cage C 60 at 200 • C under a pressure of 800 atmosphere ( figure 1, step d) [5]. Compound 3 is a nanocontainer of a hydrogen molecule, holding hydrogen unless it is heated to temperatures higher than 150 • C.…”
mentioning
confidence: 95%
“…Murata et al investigated the synthesis, structure, and properties of novel open-cage fullerenes with heteroatom on the rim of the orifice [13] as well as the feasibility of inserting small atoms or molecules through the orifice of an open-cage C 60 derivative. Hatzimarinaki et al reported a novel methodology for the preparation of five-, seven-, and nine-membered fused rings on C 60 fullerene [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular hydrogen was successfully placed inside open-cage fullerenes [13,[15][16][17][18][19][20][21]. Murata et al [16] reported the first syntheses and X-ray structures of organic and organometallic derivatives of C 60 and the usage of the encapsulated molecular hydrogen as a magnetic shielding probe.…”
Section: Introductionmentioning
confidence: 99%